Lucifensin, klíčová molekula larvální terapie - Čeřovský, Václav (Vesmír, 2011)
The beneficial use of fly larvae in healing chronic infected wounds has been known since ancient times, but reintroduction of standard, routine maggot therapy in clinical practice at hundreds of hospitals around the world dates back only to the 1990s. The application of Lucilia sericata larvae into infected wound results in removal of necrotic tissue, elimination of infecting microorganisms, disinfection of the wound, and stimulation of wound granulation and repair. Many researchers have focused on the study of antimicrobial compounds secreted/excreted by maggots to the wound. The antimicrobial peptide of larval immune system named lucifensin secreted/excreted to the wound was for the first time identified by scientists of the Institute of Organic Chemistry and Biochemistry, Academy of Sciences of the Czech Republic. Discovery of lucifensin contributes to the understanding of healing principles of larval therapy.
Keywords: larva; Anti-Infective Agents; Wound Healing; Larva; Antimicrobial Cationic Peptides; Humans; antiinfekční látky; Therapy with Helminths; kationické antimikrobiální peptidy; hojení ran; helmintoterapie; lidé